Pengaruh Cyber Public Relations DPR RI Terhadap Pemenuhan Kebutuhan Informasi Followers Akun Instagram @DPR_RI - Allana Haura Redhita; Istisari Bulan Lageni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The House of Representatives of the Republic of Indonesia has adopted various digital communication strategies to maximize the use of social media. One of the strategies implemented is Cyber Public Relations Instagram @dpr_ri seeks to utilize every opportunity provided by social media platforms to deliver accurate, relevant, and interesting information to the public.The purpose of this study is to measure Cyber Public Relations of DPR RI on the @dpr_ri Instagram account, Fulfillment of information needs of followers of the @dpr_ri Instagram account, and How much influence does cyber public relations of DPR RI have on fulfilling the information needs of followers of the @dpr_ri Instagram account. The theories used in this research are Cyber Public Relations Theory, Philips & Young (2009) and Information Needs, Guha (1978). The approach in this study uses a quantitative approach. The method used in this research is a survey. Data collection by providing questionnaires to followers of the @dpr_ri Instagram account. Based on the calculation results of the research data, the tcount value of 5.095 is greater than the ttable value of 1.668. Then H0 is rejected and H1 is accepted. So the results show that there is an influence of cyber public relations of the DPR RI on Fulfilling the Information Needs of Followers of the @dpr_ri Instagram account.There is data from the coefficient of determination showing that the equation is 37.7% while the remaining 62.3% is influenced by other factors outside the study.There is a strong influence between cyber public relations of the DPR RI and Fulfilling the information needs of Followers of the @dpr_ri Instagram account.